The Elephant in the Room; Preaching or Working on Climate Change (Global Journal of Science Frontier Research, 2023)
To lead people walk behind them Lao Tzu A lot has been debated about the effects of carbon emissions and their impact on climate change Of all issues that need to be addressed the one that stands out refers to the power sector which absorbs more primary energy than any other sector and accounts for anywhere between a third and half of carbon emissions worldwide At stake is the need to assure continued economic development and ensuring the associated improvements in standards of living while doing so with declining carbon emissions Over the decades growth has been propelled by massive expansion of energy demand powered by hydrocarbons that brought about increases in CO2 emissions Achieving both growth and decarbonizing economies will be one of the most challenging developments over the coming decades In recent years a growing consensus has emerged on the need to reverse growth of emissions to prevent global atmospheric conditions from generating further temperature increases To this end 195 countries entered into an international agreement in Paris to limit temperature increase 1 5 degrees Centigrade of pre-industrial levels by mid-century but there is still a long way to go to cap global warming at this level and thus no basis for complacence
Keywords: climate change conference of the parties (COP); carbon dioxide (CO2) and Green House Gas (GHC) emissions